2013
DOI: 10.1111/nmo.12091
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to abdominal pain in gastroparesis: contrast to patients with predominant nausea and vomiting

Abstract: Background Factors associated with abdominal pain in gastroparesis are incompletely evaluated and comparisons of pain versus other symptoms are limited. This study related pain to clinical factors in gastroparesis and contrasted pain/discomfort- with nausea/vomiting-predominant disease. Methods Clinical and scintigraphy data were compared in 393 patients from 7 centers of the NIDDK Gastroparesis Clinical Research Consortium with moderate-severe (Patient Assessment of Upper Gastrointestinal Disorders Symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
115
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 47 publications
(155 reference statements)
2
115
2
Order By: Relevance
“…10,35 Patient defined pain predominance was found in approximately 20% of patients referred to the NIDDK (National Institute of Diabetes and Digestive and Kidney Diseases) Gastroparesis Clinical Research Consortium. 10 Visceral hypersensitivity, defined as lowered threshold for eliciting visceral pain, is common among functional GI disorders, including functional dyspepsia and IBS. The presence of visceral hypersensitivity was found in 29% of patients with idiopathic gastroparesis 35 and 55% of patients with diabetic gastroparesis.…”
Section: Abdominal Painmentioning
confidence: 99%
See 2 more Smart Citations
“…10,35 Patient defined pain predominance was found in approximately 20% of patients referred to the NIDDK (National Institute of Diabetes and Digestive and Kidney Diseases) Gastroparesis Clinical Research Consortium. 10 Visceral hypersensitivity, defined as lowered threshold for eliciting visceral pain, is common among functional GI disorders, including functional dyspepsia and IBS. The presence of visceral hypersensitivity was found in 29% of patients with idiopathic gastroparesis 35 and 55% of patients with diabetic gastroparesis.…”
Section: Abdominal Painmentioning
confidence: 99%
“…However, in a large multicenter cohort study, the prevalence of moderate-to-severe abdominal pain (approximately 60%) was similar between patients with idiopathic and diabetic gastroparesis. 10 In this study, 20% of patients with gastroparesis reported pain predominance compared with 44% reporting nausea/vomiting predominance. The presence of pain predominance was associated with decreased quality of life and increased depression and anxiety.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…10 Nausea and/or vomiting represent the predominant symptoms, prompting specialist referral of 44% of patients ( Table 1). 11 In a single-center study, nausea scores averaged 3.4 (on a scale from 0 to 5) over 8 hours daily in patients with both diabetic and idiopathic gastroparesis. 10 Mean daily vomiting frequencies ranged from 3.5 with idiopathic disease to 7.3 for diabetics with gastroparesis.…”
Section: Antiemetic Agentsmentioning
confidence: 99%
“…The clinical impact of gastroparesis is significant; symptoms, particularly pain, are associated with impaired quality of life and increased anxiety or depression [11] while examination of national trends has shown a > 200% increase in overall hospitalizations for gastroparesis [12]. There remains a need for development of effective and targeted pharmacologic treatments.…”
Section: Introductionmentioning
confidence: 99%